2018
DOI: 10.1177/1098214018796342
|View full text |Cite
|
Sign up to set email alerts
|

Transparent, Translucent, Opaque: Exploring the Dimensions of Power in Culturally Responsive Evaluation Contexts

Abstract: The concept of power is a complex and often intangible aspect of the evaluation process that is frequently a focal topic among the conceptual evaluation literature concerning collaborative or culturally responsive evaluation (CRE) contexts. Unfortunately, there remains a significant theory to practice gap as power is often rarely addressed or specifically identified in empirical practice. In the current article, the authors provide a comprehensive review of the empirical literature on CREs, with an emphasis on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…Gobo (2011), Beeman-Cadwallader, Quigley and Yazzie-Mintz (2011), Smith (2012, Lincoln and González (2008) and Katz et al (2016) also identified different ranges of customised qualitative research strategies that can be considered as good practices for these purposes. Stickl Haugen and Chouinard (2018) propose a number of concrete evaluation design and implementation strategies to reduce the unequal power relationships frequently inherent in culturally responsive evaluations.…”
Section: Decolonisation Of Research and Evaluationmentioning
confidence: 99%
“…Gobo (2011), Beeman-Cadwallader, Quigley and Yazzie-Mintz (2011), Smith (2012, Lincoln and González (2008) and Katz et al (2016) also identified different ranges of customised qualitative research strategies that can be considered as good practices for these purposes. Stickl Haugen and Chouinard (2018) propose a number of concrete evaluation design and implementation strategies to reduce the unequal power relationships frequently inherent in culturally responsive evaluations.…”
Section: Decolonisation Of Research and Evaluationmentioning
confidence: 99%
“…Culturally responsive evaluation should engage community members in a meaningful manner, and acknowledge the cultural context of the evaluation (Stickl Haugen & Chouinard, 2019). Most importantly, evaluators are encouraged to build trusting relationships with stakeholders and support their capacity to learn and understand the purpose and impacts of the work (Campbell & Wiebe, 2021).…”
Section: Recommendationsmentioning
confidence: 99%
“…Those working with marginalised populations must carefully consider the issues of equity and social justice, and aim to minimise the unequal power relations present between evaluators and stakeholders (Thomas & Parsons, 2017). Culturally responsive evaluation should engage community members in a meaningful manner, and acknowledge the cultural context of the evaluation (Stickl Haugen & Chouinard, 2019). Most importantly, evaluators are encouraged to build trusting relationships with stakeholders and support their capacity to learn and understand the purpose and impacts of the work (Campbell & Wiebe, 2021).…”
Section: Recommendationsmentioning
confidence: 99%
“…Such reflection could lead to the disruption and rejection of the status quo; a challenging of discursive, temporal, relational, and political power (Stickl Haugen & Chouinard, 2019); and a centering of social justice as fundamental in evaluation (Boyce & Chouinard, 2017;Mertens & Hopson, 2006). To effectively measure DEI in evaluation contexts, we need to be willing, able, and ready to facilitate critical reflection on what is going well, what is not going well, and what could be done to improve programmatic attention toward diversity, equity, and inclusivity.…”
Section: Conclusion: Promoting Reflective Practice and Centering Deimentioning
confidence: 99%